Comparing the influence of front-of-pack nutrition labels on Saudi consumers’ understanding and food selection - AlQurashi, Alaa Ashraf; Marar, Sumayyia D.; Ayyash, Mohsen; AlRawi, Halah Z.; Abu-Shaheen, Amani (Frontiers in Public Health, 2025)
IntroductionFront-of-pack labels (FoPLs) are key public health tools that help consumers identify healthier food options. Although widely studied, little is known about their effectiveness in Saudi Arabia. This study aimed to determine the most understandable FoPL among five international systems to help Saudi consumers make healthier food choices.MethodsFrom January 1, 2022, to January 30, 2023, 2,509 Saudi consumers aged 18 years and above were recruited in public places across Riyadh. Participants were asked to select one product from sets of five food categories (bread, cheese, cereals, nuggets, and juice) with different nutritional profiles and then rank the products within each set based on their perceived nutritional quality. These tasks were first performed without any FoPL. Participants were then randomly assigned to one of the following five FoPL systems: Health Star Rating (HSR), Guideline Daily Amount (GDA), Multiple Traffic Lights (MTL), Chilean Warning Octagons (CWO), or Nutri-Score (NS), and asked to repeat the same tasks with the assigned label displayed on the packaging. Multivariate ordinal logistic regressions were performed to analyze whether changes in the scores of food choices and the ability to correctly rank the products were associated with the FoPL types, along with various socioeconomic and behavioral factors.ResultsThe analyses showed that participants improved their food choices depending on the FoPL format and the food category. Nutri-Score (NS) demonstrated a significant improvement in food choices across all food categories (OR = 1.96, 95% CI: 1.24 to 3.17, p = 0.003), particularly for nuggets (OR = 2.18, 95% CI: 1.16 to 3.17, p = 0.038) and cereals (OR = 2.16, 95% CI: 1.28 to 4.53, p = 0.001), compared to the GDA label. All FoPL types resulted in a greater proportion of correct responses in the ranking task compared to the no-label condition. Furthermore, NS emerged as the most influential FoPL in enhancing participants’ understanding of nutritional quality, significantly improving their ability to correctly rank products across all food categories (OR = 5.81, 95% CI: 2.92 to 7.28, p < 0.001).ConclusionThe study suggested that the presence of FoPLs can enhance consumers’ ability to evaluate the nutritional quality of food products. In particular, the study demonstrated that NS is among the most effective FoPLs that help Saudi consumers assess the nutritional quality of different food categories. Policymakers may consider adopting NS as a standard FoPL system to support healthier dietary behaviors and reduce the prevalence of diet-related diseases in Saudi Arabia.